From Concept to the Introduction of Industry 4.0 - Crnjac, Marina; Veža, Ivica; Banduka, Nikola (International Journal of Industrial Engineering and Management, 2017)
Industry 4.0 is very popular topic today because of its big influence on manufacturing.Industry 4.0 is focused on creating “smart” environment within production system. Several priority areas of action, inorder to get closer to the state of Industry 4.0. are shown. There are also the most important changes, that will occur in the manufacturing operations and information technology. Someleading manufacturers of technology for Industry 4.0 are presented. Many papers explore new business concepts and strategies for adaption to new industrial revolution. This paper provides an overview of several concepts and strategies. Different strategies and concepts selected from literature are compared in order to detect the areas that are not covered. Article history: Received (26.11.2016); Revised (08.02.2017); Accepted (02.03.2017)